WEB APP PENDETEKSI JENIS SERANGAN JARINGAN KOMPUTER DENGAN MEMANFAATKAN SNORT DAN LOG HONEYPOT - Asmah Akhriana; Andi Irmayana (CCIT Journal, 2019)
Along with the current development of Information Technology is always changing to make the security of an information is very important, especially on a network connected to the internet. But what is unfortunate is that the imbalance between each development of a technology is not accompanied by developments in the security system itself, so that there are quite a lot of systems that are still weak and have to be increased by the security wall. This study aims to design a Web-based App interface to facilitate users or administrators in securing network computers from various types of attacks. The Instrusion detection system (IDS) method is used to detect suspicious activity in a system or network using snort and honeypot. Honeypot is built on a computer along with Apache, MySQL, and Snort. Honeypot will act as a target to attract attackers and log information from the attacker and snort to apply the rules made from the web. The functional system will then be tested using the black box testing method. The results of this study concluded that Web App-based interfaces that are created can be used to help users and administrators in maintaining data and information on server computers from various types of attacks on computer networks